Creative leadership of school administrators affecting the effectiveness of schools under the Khon Kaen Primary Educational Service Area Office 3 - Reamree, Supranee; Ketprom, Chartchai (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to 1) study the creative leadership of school administrators under Khon Kaen Primary Educational Service Area Office 3, 2) study the effectiveness of schools under Khon Kaen Primary Educational Service Area Office 3, and 3) study the effect of creative leadership of school administrators on the effectiveness of school administrators under Khon Kaen Primary Educational Service Area Office 3. The sample group used in this research consisted of 318 school administrators and teachers, using the comparison table of Krejci and Morgan and stratified random sampling. The data collection tool was a 5-level rating scale questionnaire with an IOC value of 1.00 and a reliability value of 0.967. The statistics used for data analysis were mean, standard deviation, Pearson product – moment correlation coefficients, and stepwise multiple regression analysis. The research found that 1) The creative leadership of school administrators under Khon Kaen Primary Educational Service Area Office 3 was at a high level overall. When considering each aspect, it was found that the aspect with the highest average value was teamwork, followed by creativity, and the aspect with the lowest average value was individual consideration. 2) The overall effectiveness level of schools under Khon Kaen Primary Educational Service Area Office 3 was at a high level. Considering each aspect, it was found that all aspects were at a high level. The aspect with the highest average value was the ability to produce students with high academic achievement, followed by the ability to adjust and develop the school to fit the environment. The aspect with the lowest average value was the ability to solve problems within the school. 3) Creative leadership of school administrators in terms of teamwork, individual consideration, and creativity has a positive effect on the effectiveness variable of the school under Khon Kaen Primary Educational Service Area Office 3 with a statistical significance of .001 and can jointly predict the effectiveness of the school by 64 percent. Which can be written as a prediction equation in the form of raw scores and standard scores as follows: Prediction equation in the form of raw scores: = .276 + .379X5 + .326X2 + .210X4 Prediction equation in the form of standard scores: = .374ZX5 + .371ZX2 + .194ZX4